Information and Communication Technologies in Tourism 2018 2017
DOI: 10.1007/978-3-319-72923-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Booking Determinants of the Airbnb Properties: An Example of the Listings of London

Abstract: The aim of this paper is to investigate the factors which influence the probability of an Airbnb property being booked using the properties in London as an example. A binomial logistic model is estimated by sequential Bayesian updating due to the large volume of the data. The results show that, in spite of the market factors revealing great influence, the attributes of the properties play a more important role in influencing the booking probability of the properties. These research findings are potentially ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…In line with earlier studies on discounts [80][81][82], the findings of the present study show that an attractive travel package price and discounts of the Go-To Travel campaign can entice a certain segment of Japanese seniors ("Trusting Seniors") to increase their visit intention. The high visit intention of this segment, in general, might also be attributed to the high affinity to factor 3 (Self-Efficacy), which is in accordance with Lu's [96] findings that a higher perceived self-efficacy reduces risk perception among seniors and consequently increases visit intention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with earlier studies on discounts [80][81][82], the findings of the present study show that an attractive travel package price and discounts of the Go-To Travel campaign can entice a certain segment of Japanese seniors ("Trusting Seniors") to increase their visit intention. The high visit intention of this segment, in general, might also be attributed to the high affinity to factor 3 (Self-Efficacy), which is in accordance with Lu's [96] findings that a higher perceived self-efficacy reduces risk perception among seniors and consequently increases visit intention.…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, intention to visit was adapted from Hsu, Kang, and Lam [79] to cover the three most realistic conditions measured by three scales each (I intend to.../I want to.../It is likely that...): (1) visit intentions without external travel incentives; (2) visit intentions with attractive prices, that is, travel packages, which are one of the most favorable ways to travel for locals; (3) visit intentions with discounts offered by a national travel campaign, such as Go-To Travel. In this context, it would be of particular interest to explore if the Japanese would be increasingly willing to visit onsen establishments through such external stimuli, as suggested by Lam and Gao [80], Wong and Law [81], and Qui et al [82]. According to Japanese experts in this project, attractive package prices are a major driving factor for travel motivation among the Japanese people, and the government travel campaign has been reported to increase national travel, as mentioned above.…”
Section: Survey Designmentioning
confidence: 93%
“…Price has played a key role in decision making. Qiu, Fan, and Liu (2018) found that the increase in price, including nightly rate and other additional fees such as extra guests' fee and security deposits decrease the probability of being booked. Unlike other additional fees, cleaning fees tend to increase the probability of being booked because cleaning fees strongly signal clean accommodations (Yao, Qiu, Fan, Liu, & Buhalis, 2019).…”
Section: H2: Hosts' Communication Attributes Affect Occupancy Ratesmentioning
confidence: 99%
“…Research on exploring traditional hotel room price determinants (D. Wang & Nicolau, 2017), as well as the determinants of performance of hotels within the tourism industry, is limited (Assaf et al, 2017). Third, there is also a growing research interest about the key determinants' influence on room pricing in the sharing economy (Horn & Merante, 2017;Möhlmann, 2015;Qiu et al, 2018;D. Wang & Nicolau, 2017).…”
mentioning
confidence: 99%